Impact of the World Antimicrobial Awareness Week on public interest between 2015 and 2020: A Google Trends analysis - Koichi Keitoku; Yoshito Nishimura; Hideharu Hagiya; Toshihiro Koyama; Fumio Otsuka (International Journal of Infectious Diseases, 2021)
Objectives: To evaluate the impact of the World Antimicrobial Awareness Week (WAAW) on public awareness of antimicrobial resistance using Google Trends analysis. Methods: The impact of WAAW on public awareness of ‘antimicrobial resistance’ (AMR), ‘antibacterial’, and ‘antibiotics’ in Japan, the UK, the United States, and worldwide from 2015 to 2020 was analyzed, using the relative search volume (RSV) of Google Trends as a surrogate. A joinpoint regression analysis was performed to identify a statistically significant time point of a change in trend. Results: No joinpoints around WAAW were identified in Japan, the United Kingdom, or the United States from 2015 to 2020 with RSVs of ‘AMR’, whereas increasing RSVs were noted worldwide in 2017 and 2020. Further, there were decreasing RSVs of ‘antibiotics’ in the first half of 2020, which could be due to the COVID-19 pandemic. The study results suggest that WAAW did little to improve public awareness of AMR in the selected countries despite its contribution worldwide. Conclusions: This study implies that we need to develop a more effective method to improve public awareness to fight against AMR.